Persuasive Advertising and Legal Gaps in Regulating Research and Thesis Ghostwriting Services on Social Media - Chamlongkun, Chatri; Pakdeenarong, Kraichak; Bunyasut, Supasak; Panurat, Phisitphon; Tengtraisorn, Chukiat; Prommeenate, Pairoch; Phansai, Wirat; Sittijuk, Pramote (Journal of Dhamma for Life, 2026)
This research aims to study the deceptive advertising practices of businesses providing commissioned research and thesis writing services on social media, as well as to analyze legal gaps and propose improvements to regulations for controlling these businesses. The sample group consisted of five legal scholars who are licensed attorneys, tasked with analyzing risky advertising messages on five main Facebook pages. The advertisements were categorized into three types of risks: doing work on behalf of the owner, guaranteeing results, and offering financial incentives. Content analysis was then conducted to examine expert opinions and trends related to these service pages. The study found that the pages had an average of 7.6 risky messages per page. Most advertising messages involved ethical and legal violations, such as phrases like "can do it for you," "guaranteed to graduate," and "price per chapter," while these pages also had large follower bases and high likes. Legal scholars pointed out that these messages posed clear legal risks because current laws do not fully cover new online business models, enforcement is limited, and cooperation with online platforms is lacking. The scholars recommended enacting specific laws to regulate commissioned research businesses, imposing stricter penalties, and establishing a dedicated agency for oversight. Meanwhile, online platforms should use AI technology to detect and remove illegal content, support legal teams in monitoring, disclose policies for transparency, and provide users with reporting channels. Policy recommendations emphasize integrating relevant agencies, training personnel, developing clear guidelines, monitoring enforcement, and promoting academic ethics to effectively prevent copyright infringement in the digital era.